Gender differences in the relationship between oral communicative competence and peer rejection: an explorative study in early childhood education. Issue 6 (1st November 2016) - van der Wilt, Femke; van Kruistum, Claudia; van der Veen, Chiel; van Oers, Bert
Abstract : This study investigated gender differences in the relationship between oral communicative competence and peer rejection in early childhood education. It was hypothesized that children with poorer oral communicative competence would be rejected by their peers more frequently and that the strength of this relationship would differ for boys and girls. A sample of N  = 54 children was tested on the Nijmegen Test for Pragmatics (NPT) to measure their oral communicative competence, defined as their ability to use language appropriately in a particular situation. Further, a sociometric method was used to measure the level of peer rejection and peer acceptance. No relationship was found between oral communicative competence and peer rejection. However, a positive relationship was observed between oral communicative competence and peer acceptance. Interestingly, this relationship only applied to boys. It is suggested that early childhood education teachers trying to enhance peer acceptance should take the promotion of oral communicative competence into account.